Pembuatan dan Karakterisasi Ko-kristal Flukonazol-Resorsinol - Fikri Alatas Alatas; Hestiary Ratih; Titta Hartyana Sutarna; Yoga Windu Wardhana; Dini Tereslina; Sundani Nurono Soewandhi (Fakultas Farmasi Universitas Pancasila, 2020)
Fluconazole (FLU), an oral antifungal widely used in the treatment of vaginitis andcandidiasis, is known to have low bioavailability due to its low solubility. The purpose of this studywas to prepare and characterize co-crystal fl uconazole-resoscinol (FLU-RES). The preparation ofco-crystal was performed by grinding together the equimolar mixture of FLU-RES which is drippedwith a few ethanol. Powder X-ray diff raction, diff erential scanning calorimetry (DSC), and polarizedmicroscopy methods were performed to characterize the formation of FLU-RES co-crystal. Relevantphysicochemical properties include solubility tests in water and dissolution tests in pH 1.2; 4.5 and6.8 buff er solution. The powder X-ray diff ractogram of FLU-RES milled result showed the presenceof new peaks and loss of the main peaks of FLU and RES. The characterization of grinding result byDSC and polarized microscopy methods also showed the co-crystal formation between FLU and RES.The solubility of FLU-RES co-crystal in water is solubility two folds more than pure FLU, while itsdissolution rate is 1.67-1.72 times faster than pure FLU.